Electronic Band Structure of Aluminium Nitride and Gallium Nitride Crystallizing in the Wurtzite and Zinc Blende Structures (Bulletin of Pure and Applied Sciences – Physics, 2019)
We have studied the electronic band structure of aluminium nitride and gallium  nitride crystallizing in the wurtzite and zinc blende structures. We have presented  theoretical study of atom and orbital projected partial density of state for the group  third nitrides. We have compared the energy distribution of electronic states in  valence and conduction bands as calculated by means of linear muffintin orbital method. The direct comparison with the appropriate density of state was presented  to indicate the extent to which we got direct information about allowed electron  states by considering the positions of the maxima and minima of the intensity in  spectra. The influence of the core level width and spectrometer broadening was also  considered. The good agreement between structures observed in spectra and  structures in the calculated density of state allowed for consistent analysis of results.  We have compared the amounts of bonding and antibonding states near the band  edges for different choices of cations and crystal structures. Since the device  applications are based mainly on wurtizite type nitride, particular attention was  given to this phase. We examined for wultzite structure the level of anisotropy in the  formed chemical bonds. Two kinds of bonds π and σ are connected directly with  bond lengths. We examined the amount of electronic states available for optical  transition as a function of crystal structure, crystallographic direction and presence  of cation semicore states. The hydridization between d and p states for different  cations and nitrogen were studied. We found that d-p interaction affected the  valence band edge and influenced magnitude of the fundamental gap. The obtained  results were compared with previously obtained results of theoretical and  experimental work and were found in good agreement.